2015
DOI: 10.1111/corg.12129
|View full text |Cite
|
Sign up to set email alerts
|

CEO Overpayment and Dismissal: The Role of Attribution and Attention

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: This study investigates the moderating role of CEO overpayment on the relationship between firm performance and CEO dismissal. We also examine how contextual factors, including compensation disclosure regulation, firm index status, and firm age, influence board attention and attribution, and consequently affect the sensitivity of CEO dismissal to firm performance. Research Findings/Insights: Using a sample of Chinese listed firms between 2002 and 2011, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 129 publications
2
29
0
Order By: Relevance
“…Finally, future research should test whether the current findings generalize to non‐U.S. countries with different cultures, socioeconomic institutions, and governance models (Bezemer, Zajac, Naumovska, van den Bosch, & Volberda, ; He & Fang, ). Such research would advance our understanding of the impact of signaling on governance outcomes in various institutional settings.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Finally, future research should test whether the current findings generalize to non‐U.S. countries with different cultures, socioeconomic institutions, and governance models (Bezemer, Zajac, Naumovska, van den Bosch, & Volberda, ; He & Fang, ). Such research would advance our understanding of the impact of signaling on governance outcomes in various institutional settings.…”
Section: Discussionmentioning
confidence: 94%
“…Selecting a CEO and, if necessary, firing a CEO are among a board's most important responsibilities. Recent studies have recognized the importance of cognitive processes in CEO dismissal (Graffin, Boivie, & Carpenter, ; Haleblian & Rajagopalan, ; He & Fang, ; Wiersema & Zhang, ). The basic argument is that CEO dismissal entails the board's assessment of his or her competencies and performance.…”
Section: A Cognitive Process In Ceo Dismissalmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, several studies have found that external observers, such as shareholders and information intermediaries, tend to make internal attributions about executives' responsibility for alleged instances of fraud (Gangloff, Connelly, & Shook, 2016;Gomulya & Boeker, 2014;Kang, 2008). Others focus on poor firm performance, finding that external observers favor internal attributions for failure, which often results in the dismissal of top executives (Hambrick & Quigley, 2014;He & Fang, 2016). Consistent with these ideas, Gibson and Schroeder (2003) find that, in the event of organizational failures, observers tend to blame upper-level, as opposed to lower-level, employees.…”
Section: Attribution Theorymentioning
confidence: 99%